Brain-targeted ursolic acid nanoparticles for anti-ferroptosis therapy in subarachnoid hemorrhage - Yong Li; Xinyi Zhu; Wei Xiong; Qingyu Zhao; Youdong Zhou; Yujia Guo; Baohui Liu; Mingchang Li; Qianxue Chen; Xiaobing Jiang; Yangzhi Qi; Qingsong Ye; et al. (Journal of Nanobiotechnology, 2024)
Abstract Background Subarachnoid hemorrhage (SAH) is a life -threatening cerebrovascular disease, where early brain injury (EBI) stands as a primary contributor to mortality and unfavorable patient outcomes. Neuronal ferroptosis emerges as a key pathological mechanism underlying EBI in SAH. Targeting ferroptosis for therapeutic intervention in SAH holds significant promise as a treatment strategy. Methods SAH model was induced via intravascular puncture and quantitatively assessed the presence of neuronal ferroptosis in the early phase of SAH using FJC staining, Prussian blue staining, as well as malondialdehyde (MDA) and glutathione (GSH) measurements. Hyaluronic acid-coated ursolic acid nanoparticles (HA-PEG-UA NPs) were prepared using the solvent evaporation method. We investigated the in vivo distribution of HA-PEG-UA NPs in SAH model through IVIS and fluorescence observation, and examined their impact on short-term neurological function and cortical neurological injury. Finally, we assessed the effect of UA on the Nrf-2/SLC7A11/GPX4 axis via Western Blot analysis. Results We successfully developed self-assembled UA NPs with hyaluronic acid to target the increased CD44 expression in the SAH-afflicted brain. The resulting HA-PEG-UA NPs facilitated delivery and enrichment of UA within the SAH-affected region. The targeted delivery of UA to the SAH region can effectively inhibit neuronal ferroptosis, improve neurological deficits, and prognosis in mice. Its mechanism of action is associated with the activation of the Nrf-2/SLC7A11/GPX4 signaling pathway. Conclusions Brain-targeted HA-PEG-UA NPs was successfully developed and hold the potential to enhance SAH prognosis by limiting neuronal ferroptosis via modulation of the Nrf-2/SLC7A11/GPX4 signal. Graphical Abstract